BLUE-PRINT PEMBELAJARAN SEJARAH BERBASIS KONTROVERSI - Wijaya, Daya Negri (Vidya Karya, 2016)
Abstract: History teachers often avoid the controversial material in history learning. This phenomenon did not happen by accident but constructed by some perspectives in writing the past. One of the topics which are full of controversy is that of the era of England colonization in Nusantara. This controversy was raised due to the degradation of the sense of history among educators. Educators actually should be able to dig the historical resources independently and explain the various perspectives clearly. The author, by the help of re-enactment theory, offerred a way in understanding a controversial material through the topic of England colonization. The author hopes that the students will be able to imagine and understand the various controversy in history learning especially in the era of England colonization. Keywords: England colonization, re-enactment, and controversy Abstrak: Materi sejarah yang sarat akan kontroversi seringkali dihindari oleh guru. Kecenderungan ini bukan suatu kebetulan akan tetapi dikonstruksi oleh berbagai perspektif dalam menuliskan masa lalu. Salah satu materi sejarah yang sarat akan kontroversi adalah masa penjajahan Inggris di Nusantara. Kontroversi tersebut muncul karena degradasi sense of history pendidik. Mereka seyogyanya menggali sumber-sumber sejarah secara mandiri dan mampu menjelaskan perbedaan perspektif tersebut dengan baik. Dengan bantuan teori re-enactment, penulis menawarkan cara dalam memahami materi kontroversial dengan contoh kasus materi kolonialisme Inggris. Penulis berharap siswa akan dapat membayangkan dan memahami beragam kontroversi pada materi sejarah terutama masa penjajahan Inggris. Kata-kata kunci: kolonialisme Inggris, re-enactment, dan kontroversi